PENERAPAN METODE PENUGASAN (ASSIGNMENT) UNTUK OPTIMALISASI PEMBAGIAN TUGAS PELAYANAN DAN PERTUMBUHAN JEMAAT GEREJA METHODIST INDONESIA PARDAMEAN SP. 5 BUANA - Yosia Suhendri Rajagukguk (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The growth of the church congregation heavily depends on the effectiveness and efficiency of the division of service tasks. The main problem faced by the Methodist Church of Indonesia Pardamean SP. 5 Buana is the placement of servants that has not been in accordance with their respective abilities, resulting in less-than-optimal service outcomes and the potential to hinder congregational growth. This study aims to apply the Assignment method as a quantitative analysis technique to match each service program with the most appropriate work field, thereby achieving optimal results. Data processing was carried out using QM Windows software, utilizing program implementation effectiveness data from 17 types of service activities and 10 responsible work fields. The results showed that this method successfully produced the most suitable task allocation based on the strengths of each service field, with a maximum total efficiency value reaching 86. The implementation of the resulting task division can improve service quality, optimize the use of human resources, and support congregational growth both in terms of quantity and quality.